Finding the path of least resistance: an examination of officer communication tactics and their impact on suspect compliance - Foster, Jacob T. (Criminology & public policy, 2024)
Research Summary This study investigated the impact of patrol officer communication tactics on suspect compliance by using Systematic Social Observation (SSO) to code 438 body-worn camera and dashcam video recordings from two police agencies. Specifically, we examined officer tenor/demeanor, use of noncoercive directives, use of verbal coercion, and accusations, while controlling for a host of suspect and situational factors. Results showed that when officers presented a positive tenor/demeanor or employed noncoercive verbal tactics, suspects were significantly more likely to comply. Conversely, use of coercive verbal tactics and accusatory language did not have a significant impact on suspect compliance. In addition, negative suspect demeanor, suspect impairment, and suspect elevated emotional state negatively affected compliance. Policy Implications Recent calls for police reform have focused on producing less coercive outcomes by explicitly recognizing the role that officers have in managing encounters rather than simply reacting to suspect behaviors. An increased focus on officer communication strategies in both police training and practice is likely to promote suspect compliance while reducing the need for officer use of force. Similarly, it is likely that more coercive verbal strategies have little impact on suspect compliance and may lead to negative perceptions of police interactions and law enforcement in general.